Analisis Disparitas Gender Terhadap Pertumbuhan Ekonomi Indonesia - Octaviyani, Mira Luh; Endang, Endang (Universitas Batanghari Jambi, 2024)
In developing economy, qualified human resources are needed, but gender inequality is a problem that must occur in every country so that the Government must make several efforts to equalize between genders, especially in the fields of health, education, and decent living standards. The aims of this research is to compare the gap between gender inequality that occurs and its impact on economic growth in Indonesia. The data used in this study are data sourced from BPS in 2017 to 2022 and processed using EViews 12 with panel data regression data analysis. This study found that female & male AHH (X1) had a positive and insignificant effect on economic growth (Y), male & female RLS (X2) had a negative and significant effect on economic growth (Y), and male PLP (X3) had a positive but insignificant effect and female PLP (X3) had no but significant effect on economic growth (Y) in Indonesia.